Survey on Sharīʿah non-compliant events in Islamic banks in the practice of tawarruq financing in Malaysia - Ali, Mohammad Mahbubi; Hassan, Rusni (Emerald Group Holdings Ltd., 2020)
Purpose: Tawarruq (Islamic commodity financing) has evolved as the most ubiquitous concept in Malaysia’s Islamic banking industry. Nevertheless, the extensive use of tawarruq has invoked a number of Sharīʿah (Islamic law) concerns in its practice. This study aims to investigate the Sharīʿah non-compliant (SNC) phenomena in the practice of tawarruq financing in Malaysia. Design/methodology/approach: This study adopts qualitative research methodology, combining both descriptive and content analysis. A self-administered questionnaire was distributed to 16 Malaysian Islamic commercial banks to unveil the Sharīʿah non-compliance issues in the application of tawarruq in Islamic banks (IBs) in Malaysia. Findings: The study found that some practices of tawarruq in Malaysia might not comply with the Sharīʿah, mainly due to the improper sequencing of contracts. The study also discovered that IBs adopt different approaches in dealing with SNC events and the income derived therefrom. Finally, the study noted the influence of board of director/management on certain Sharīʿah decisions particularly on the treatment of non-ḥalāl (impermissible) income. Practical implications: The findings of the study serve as a reference to industry players and regulators in formulating a Sharīʿah non-compliance risk management framework for tawarruq practices. Originality/value: The survey on SNC issues in tawarruq practice constitutes the first of its kind in the existing literature